Effect of organizational changes on employees’ motivation at a Country Club in Kwazulu Natal: from the employees’ participation perspectives - Orthodox Tefera; Emmanuel Mutambara (African Journal of Hospitality, Tourism and Leisure, 2016)

(untitled)
Organizations undergo a change that may or may not subscribe to the values of organizational development (OD) and, in many instances, are not accomplished by participative processes. For most of them organizational change has become synonymous with downsizing by cutting expenses and retrenching employees and therefore trepidation by those who are likely to be affected. Employees are integral to ensure the efficiency and effectiveness of an organization. Therefore, if employees perceive that the organizational change is not properly communicated to them, it is likely that their motivation will be affected and may be counter-productive to the objective of the change process. This paper evaluated the strategic change management implementation at a country club in Kwazulu Natal; the employees’ participation in the process and its impact on employees’ motivation. The quantitative research method with descriptive analysis was administered on a sample of eighty country club employees. The key findings of the study reveal that the management had not created opportunities for employees to participate. Employees felt that they could have made contribution if they were consulted. Employees felt demotivated because of poor communication. Even though the employees felt that the organizational change would help the club to achieve its goals, the club was not able to achieve its financial targets. Employees felt more motivated after the organizational change and the challenge for the management is to ensure that the employees are kept motivated.